Sosialisasi Edukasi Profesi untuk Meningkatkan Wawasan Cita-Cita Siswa di SDN Sukowati - Dahlia Zahrotul Jannah; Lusi Nur Indrawati; Anas Fadilah Ramadhon; M. Faisal Farid Dhihri (Nawasena Bhakti, 2025)
Elementary school students' lack of understanding about the importance of having goals and recognizing various professions can result in low motivation to learn and unpreparedness in planning for the future. This is also experienced by students at SDN Sukowati, where several teachers said that some students did not have purposeful goals. This condition shows the need for an educational approach that is fun and in accordance with the characteristics of elementary school-age children. Therefore, this educational socialization was carried out with the aim of providing an understanding to elementary school students about the importance of having goals and getting to know various professions early on. The socialization took place at SDN Sukowati, Bojonegoro Regency, with an implementation method that includes preparation, implementation (interactive lectures, guess the profession games, discussions and questions and answers,) and evaluation (analysis of pre-test and post-test question results). The results of the socialization activities showed that students were very enthusiastic, active in discussions, and able to express their ideals in a more directed manner after attending the socialization.